1999
DOI: 10.1116/1.590851
|View full text |Cite
|
Sign up to set email alerts
|

Surface potential of ferroelectric thin films investigated by scanning probe microscopy

Abstract: Scanning probe microscopy was used to form local polarized domains in ferroelectric thin films by applying a voltage between the gold-coated cantilever and the conductive substrate in contact mode. Two methods of visualizing the poled areas are described. The first is to detect the piezoelectric response of the films by applying a small oscillating voltage between the probe tip and the substrate. This measurement determines the local ferroelectric polarity and domain structure directly. The second method is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 20 publications
2
101
0
Order By: Relevance
“…[73][74][75][76][77] Clearly, elucidating the charge effects in the PFM requires a reliable way to probe the local piezoresponse and long-range electrostatic forces simultaneously. This is especially important for investigations of dynamic phenomena in which large time intervals between sequential PFM-SSPM images are unacceptable.…”
Section: Figmentioning
confidence: 99%
“…[73][74][75][76][77] Clearly, elucidating the charge effects in the PFM requires a reliable way to probe the local piezoresponse and long-range electrostatic forces simultaneously. This is especially important for investigations of dynamic phenomena in which large time intervals between sequential PFM-SSPM images are unacceptable.…”
Section: Figmentioning
confidence: 99%
“…SPM has been successfully applied to semiconductor, 19 organic, 20 and ferroelectric 21,22 surfaces, as well as to defects, 23,24 and photoinduced 25,26 and thermal phenomena 27,28 in these materials. A number of SPM studies on grain boundary related phenomena have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely believed that an overscreened surface occurs during bias-induced domain switching. 2,3,10 When a positive bias is applied on the ferroelectric films by a SPM tip, the ferroelectric polarization will points to the bottom electrode (downward-polarized). Electrons will be pulled away from the surface, and holes will accumulate and be trapped on the surface.…”
Section: Methodsmentioning
confidence: 99%
“…So far, adsorption and desorption of the surface screening charges 9 were seemed as a mechanism of SP decay process. Besides, sideways diffusion of screening charges and recombination with the opposite charges on adjacent domains 8,10 has also been proposed to play important roles in the SP decay process. Moreover, charge diffusion along the out-of-plane direction followed by the injection into the bottom electrode, as a possible mechanism, has not been ruled out yet.…”
Section: Introductionmentioning
confidence: 99%